If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 3(5x + 6) = 82 Reorder the terms: -7x + 3(6 + 5x) = 82 -7x + (6 * 3 + 5x * 3) = 82 -7x + (18 + 15x) = 82 Reorder the terms: 18 + -7x + 15x = 82 Combine like terms: -7x + 15x = 8x 18 + 8x = 82 Solving 18 + 8x = 82 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 8x = 82 + -18 Combine like terms: 18 + -18 = 0 0 + 8x = 82 + -18 8x = 82 + -18 Combine like terms: 82 + -18 = 64 8x = 64 Divide each side by '8'. x = 8 Simplifying x = 8
| 2b=19.6 | | -2(3x-4)+3(5x-1)= | | -5x+7=3x-5 | | 6+3x=8+-14 | | x^5-4x^4-32x^3= | | w+2.75=13.13 | | .24=log(x) | | 4-(x-5)=3(x-11) | | [5x]=10 | | 18-2x=x+19 | | q-1.53=7.04 | | 4.33b=495 | | r+1=7.85 | | 4=-8n | | 13x-3=5x-6 | | 6(x-9)=-30 | | 4.33=495 | | 6+-7=8 | | 16x-3=7x+6 | | 4(36+9y)=-72 | | -7/83/4 | | 4r-6-3=4r-9 | | a(z+5)=32 | | 4x-13=3x-1 | | d−8/−2=12 | | 4(x+6)=3x+4 | | c+3=3(11-3c) | | 6.1=u-3.3 | | x+5y=4z | | 1/2(1/4) | | -9x-6=6x+9 | | 5/4t=10 |